Evaluation of functional disability and pain in patients with chronic low back pain submitted to physiotherapy - Teixeira, Andrei Luiz Sales; Silva, Noberto Fernandes da; Filho, Edson Meneses da Silva (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Chronic low back pain (CLBP) is one of the causes that usually result in mobility limitations in the economically active population due to musculo-skeletal disorders. It has, as main symptoms, pain and disability and should be seen as a public health problem. Objective: This study aimed to evaluate the Functional Disability (FD) and pain intensity in patients with CLBP, underwent to manipulative therapy and conventional physiotherapy at Getulio Vargas Hospital. Method: This was a randomized trial study with a control group, with a sample, participants with CLBP, who were divided into two groups: those who underwent manipulative physiotherapy (group 1) and those who underwent conventional therapy (group 2), and the both groups were subjected to two treatments at different times. The program lasted five weeks, and 2 weeks for each intervention, performing two weekly sessions, which average duration was 30 minutes and one week interval between treatments. There were collected sociodemographic data, data related to FD using the Disability questionnaire Roland-Morris (RMDQ) and data related to pain intensity using the Visual Analogue Scale (VAS). Results: The study included 14 patients with mean age of 51 + 9 years. They showed significant improvement in RMDQ (p <0.001) and VAS (p <0.001), after being subjected to manipulative group, also showing a significant treatment effect over conventional treatment in both RMDQ (p = 0.004) and EVA (p = 0.006). Conclusion: Through this study, it can be shown that patients with CLBP showed significant improvements in functional capacity, by reducing the FD and reduction of painful symptoms, after being subjected to a five-week-program of manipulative physiotherapy.